﻿Pullimosina (Pullimosina) turfosa sp. nov. and other Sphaeroceridae (Diptera) from peat bogs in the North Caucasus (Russia) - Roháček, Jindřich; Przhiboro, Andrey A (ZooKeys, 2022)
The first data about Sphaeroceridae occurring on eight montane and foothill peat bogs of various types in the North Caucasus (Russia) are presented. A total of 38 species has been recorded and their affinity to peat-bog habitats is discussed. A single species is classified as a tyrphobiont, viz. the strongly brachypterous Pullimosina (Pullimosina) turfosasp. nov. being strictly associated with Sphagnum hummocks in peat bogs. This new species is described and illustrated in detail and its relationships, biology, and wing reduction are discussed. Only three species are considered tyrphophilous or probably tyrphophilous, viz. Ischioleptanitida (Duda, 1920), Phthitia (Kimosina) longisetosa (Dahl, 1909), and Spelobiaibrida Roháček, 1983. The majority of recorded species do not have close affinity to peat bogs and are treated as tyrphoneutral, and Rachispodahostica (Villeneuve, 1917) is probably tyrphoxenous due to occasional occurrence in a peat bog. Species composition of Sphaeroceridae on Caucasian peat bogs is discussed in comparison to those known from peat bogs in other parts of Europe. Taxonomic notes are given on Minilimosina (Svarciella) species of the M.vitripennis group. Six species (including P.turfosa sp. nov.) are new additions to the fauna of Russia.
Keywords: distribution; brachyptery; taxonomy; lesser dung flies; tyrphophily; Limosininae; relationships; biology